STUDI RENCANA PENGEMBANGAN KAWASAN EKOWISATA DI DESA PAGATAN BESAR - Frisca Septiana Pratiwi; Abdi Fithria; Wahyuni Ilham (Jurnal Sylva Scienteae, 2022)
Pagatan Besar is a village located in Takisung District, Tanah Laut Regency which has potential tourist attractions to be developed as an ecotourism area. It has potential landscape, flora, and fauna that can be developed as a tourist attraction. The existence of a potential tourist attraction in Pagatan Besar Village can be used as a study to develop an ecotourism area with the right strategy. This study aims to analyze the development plan of potential tourist attraction objects in Pagatan Besar Village. Data collection was done by field observations and interviews. Respondents were determined by the purposive sampling method. The results of the data were analyzed descriptively qualitatively and using SWOT analysis. Pagatan Besar Village has a potential tourist attraction, namely mangrove ecotourism, coastal tourism, and river areas that have not been developed. Based on the calculation of IFAS and EFAS, the internal factor value is 1.53 and the external factor is 1.58. The SWOT analysis results show that Pagatan Besar Village is in quadrant I, so the chosen strategy is the S-O strategy. Strategies that can be input in efforts to develop ecotourism include improving facilities and infrastructure, developing and providing tour packages, providing training and counseling to the community, and building facilities for the preservation of flora and faunaDesa Pagatan Besar merupakan salah satu desa di Kecamatan Takisung, Kabupaten Tanah Laut yang memiliki potensi objek daya tarik wisata yang dapat dikembangkan sebagai kawasan ekowisata. Terdapat potensi lanskap serta flora dan fauna yang bisa menjadi daya tarik. Adanya potensi objek daya tarik wisata di Desa Pagatan Besar dapat dijadikan kajian untuk mengembangkan sebuah kawasan ekowisata dengan strategi yang tepat. Penelitian ini bertujuan untuk menganalisis rencana pengembangan potensi objek daya tarik wisata di Desa Pagatan Besar. Pengambilan data dilakukan dengan observasi lapangan dan wawancara. Responden ditentukan dengan metode Purposive Sampling. Hasil data dianalisis secara deskriptif kualitatif dan menggunakan analisis SWOT. Desa Pagatan Besar memiliki potensi daya tarik wisata yaitu ekowisata mangrove, wisata pantai dan kawasan sungai yang belum dikembangkan. Berdasarkan perhitungan IFAS dan EFAS, diperoleh nilai faktor internal sebesar 1,53 dan faktor eksternal sebesar 1,58. Hasil analisis SWOT menunjukkan Desa Pagatan Besar berada pada kuadran I, sehingga strategi terpilih adalah strategi S-O. Strategi yang dapat menjadi masukan dalam upaya pengembangan ekowisata diantaranya perbaikan sarana dan prasarana, mengembangkan dan menyediakan paket wisata, memberikan pelatihan dan penyuluhan kepada masyarakat, serta pembangunan fasilitas untuk pelestarian flora dan fauna